Mahler i odebranie Dziewiątej Symfonii - Berger, Karol (Res Facta Nova, 2025)
The last word of Mahler’s Fifth Symphony, composed in 1901–02 and premiered in 1904, is ironic, mocking even, certainly not pompously triumphant. What is mocked here is the whole tradition of victorious symphonic scenarios epitomized by Beethoven’s Ninth Symphony, the “per aspera ad astra” tradition that had symphonists propose stories of suffering triumphantly overcome. The Finale also puts into question Mahlers own past. For the first time, the composer writes here a symphony that does not aim at a transcendence and sublimity, but accepts the comic immanence of the earthly existence. The aspiration to transcendence fails, but is not forgotten, and neither are the negative aspects of human existence that gave rise to this aspiration Keywords Gustav Mahler, Fifth Symphony, Second Symphony, Ludwig van Beethoven, Ninth Symphony, the “per aspera ad astra” tradition, Friedrich Schiller, Ode to Joy, Johann Wolfgang Goethe, Faust, neo classicism, rondo-finale